Analysis of Factors Influencing Indonesian Coffee Export Volume Abroad - Mutiara Sari Lubis; M. Syafii; Sukardi (International Journal of Scientific Multidisciplinary Research, 2023)
The aim of this research is to analyze factors influencing Indonesian coffee export volume abroad. The type of data used in this research is quantitative secondary data. Data taken from the Indonesian Central Statistics Agency, World Bank, United Nations International Trade Statistics Database, Indonesian Shoe Association, and United Nations Conference on Trade and Development. This research uses the literature study method, by analyzing secondary data obtained from official publications related to this research. The data analysis method in this research uses panel data regression. The research results show that real gross domestic product has a positive and significant effect on Indonesian coffee export volume abroad. Exchange rate has a positive and significant effect on Indonesian coffee export volume abroad. Price has a negative and significant effect on Indonesian coffee export volume abroad. Population has a positive and significant effect on Indonesian coffee export volume abroad